SejarahNovel Sejarah Indonesia: Komunikasi antara Dunia Sastra dengan Dunia Nyata - Heru Marwata (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2008)
Literary works bring their spirit of age. Its mean that literary works cant be separated from certain time context. So,thereâ€™s communication between literary and reality. Then, can we use â€œhistoryâ€ on literary works as a source of history? Severalpeople agree that literary can be positioned as mental fact. Therefore, with certain consideration, with certain filter, andcomparison and evaluation process, thereâ€™s chance that literary, or historical fact inside literary works, being used as onesecondary historical source.